Quantum-statistical line shape calculation for Lyman-a lines in dense H plasmas - Lorenzen, S.; Wierling, A.; Reinholz, H.; Röpke, G.; Zammit, Mark; Fursa, Dmitry; Bray, Igor (2012)
We present results for the Lyman-a line of hydrogen in dense plasmas. Full line profiles are calculated within a quantum-statistical method, based on thermodynamic Green's functions. The contributions of plasma ions and electrons are considered separately. Linear and quadratic Stark effect as well as quadrupole effects are taken into account for ions. The model microfield method is used to include ion dynamics. The focus of this work lies on the contribution to broadening and shift by free electrons beyond the Born approximation. The effect of strong collisions can be identified as ladder-like diagrams of the electron-emitter propagator. In an effective two-particle approximation, the electronic self-energy is given in terms of scattering amplitudes, analogous to Baranger's expressions [Baranger, M 1958 Phys. Rev. 112 855]. We obtained scattering amplitudes from convergent close-coupling calculations including medium effects via Debye screening. Additionally, the electronic coupling between initial and final states is taken care of by a vertex correction. In our examples, the free electron density ranges between 1023 and 10 25 m-3 at a plasma temperature of 1 and 2 eV, respectively.